Anti-Racist Alliances against white Domination in the Cultural Sector (KULT_online, 2020)
In the bilingual anthology Allianzen. Kritische Praxis an weißen Institutionen artists, curators, and scholars reflect on their cooperation with white cultural- und educational institutions. The contributions cover structural racism in the institutions and critical artistic interventions. The publication is part of the international theater project Afropean Mimickry & Mockery at Künstlerhaus Mousonturm in Frankfurt am Main and is edited by the organizers of the project. The volume addresses an academic audience as well as practitioners in the cultural sectors who want to critically engage with the colonial continuity of their institutions.